2006
DOI: 10.1111/j.1365-2265.2006.02513.x
|View full text |Cite
|
Sign up to set email alerts
|

Gamma knife radiosurgery for acromegaly – long‐term experience

Abstract: In acromegaly, LGK is a useful adjunct to primary neurosurgery when treating post-surgical residues because it can limit the duration of medical therapy. It can be used as a primary therapy when neurosurgery is not possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
101
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(120 citation statements)
references
References 58 publications
(68 reference statements)
17
101
2
Order By: Relevance
“…1,7,8,10,16,19,22,23,[25][26][27][28]30,33,34,[37][38][39][40][41][42]45,[47][48][49]51 The mean reported patient age was 45.2 ± 3.78 years. The overall mean duration of reported follow-up was 48.5 ± 25.8 months, and the overall median duration of reported follow-up was a similar 46.6 ± 20.4 months.…”
Section: Results Of Systematic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…1,7,8,10,16,19,22,23,[25][26][27][28]30,33,34,[37][38][39][40][41][42]45,[47][48][49]51 The mean reported patient age was 45.2 ± 3.78 years. The overall mean duration of reported follow-up was 48.5 ± 25.8 months, and the overall median duration of reported follow-up was a similar 46.6 ± 20.4 months.…”
Section: Results Of Systematic Analysismentioning
confidence: 99%
“…If the experience from Cushing disease is any indication, in which short-term surgical remission rates of > 75% reported by many authors is contrasted by long-term data that suggests that the recurrence rate exceeds 50% short-term remission rates reported in acromegaly series must be regarded accordingly. 5,6,9,14,15,25,31,35,44 This is especially true for older series using less stringent biochemical outcome criteria. As a result, there will be a significant proportion of surgical patients who either fail to achieve remission or have disease recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This high variability can be attributed to different treatment schedules, criteria of cure or follow-up durations. GK treatment induces tumor shrinkage in about 60-75% of cases (Jezkova et al 2006, Lee et al 2014a) at 5-6 years and the percentage continues to increase slowly up to 82% at 8 years (Lee et al 2014a). The biochemical control rate is more difficult to be appreciated because various control criteria were used; a crude estimate from the largest studies published suggest biochemical control with GK in about 48% after a mean follow-up of 4 years (Newell-Price 2009).…”
Section: Medical Treatmentmentioning
confidence: 99%
“…With Gamma Knife radiosurgery, biochemical remission rates (without the need for medical therapy) are reported to be 10-60 % over a 5-year follow-up period. [57][58][59] It has been suggested that time to remission is shorter with Gamma Knife radiosurgery than with conventional radiotherapy, although this is not entirely clear. 57,59 Radiosurgery is generally considered if the tumor is a minimal distance from the optic chiasm resulting in an exposure of more than 800 cGy.…”
Section: Radiation Therapymentioning
confidence: 96%